2000
DOI: 10.1212/wnl.55.12.1801
|View full text |Cite
|
Sign up to set email alerts
|

Can emergency department physicians safely and effectively initiate thrombolysis for acute ischemic stroke?

Abstract: Background: The 3-hour window for treating stroke with intravenous tissue plasminogen activator (t-PA) requires well-organized, integrated efforts by emergency physicians and stroke neurologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 14 publications
0
37
0
1
Order By: Relevance
“…Similar analyses have already been performed for intravenous treatment. [17][18][19][20]27 Patients who were transferred directly to our stroke center were mostly residents of Bern or an area close to that vicinity. Their mean prehospital delay was 99 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar analyses have already been performed for intravenous treatment. [17][18][19][20]27 Patients who were transferred directly to our stroke center were mostly residents of Bern or an area close to that vicinity. Their mean prehospital delay was 99 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Although emergency physicians exhibit high sensitivity and positive predictive value in identifying patients with stroke, 110,111 only 6 studies [112][113][114][115][116][117] have identified instances of fibrinolytic delivery in the setting of acute stroke by an emergency or primary care physician (either alone or in telephone consultation with a neurologist). The number of patients treated by nonneurologists in these studies was small, ranging from 6 to 53.…”
Section: Access To Neurological Expertisementioning
confidence: 99%
“…31,32 Others have shown that lowering of hemorrhage rates can be achieved with significant educational support, quality monitoring, and experience. 16,[33][34][35][36] Our study suggests that tPA administration is safe in community settings, although efficacy and outcome postthrombolysis were not measured.…”
Section: Wojner-alexandrov Et Al Hopsto Studymentioning
confidence: 99%